Exploring psychosocial predictors of STI testing in University students - H. A. Martin-Smith; E. A. Okpo; E. R. Bull (BMC, 2018)
Abstract Background To explore university students' Sexually Transmitted Infection (STI) testing knowledge, psychosocial and demographic predictors of past STI testing behaviour, intentions to have an STI test, and high risk sexual behaviour, to inform interventions promoting STI testing in this population. Methods A cross-sectional, quantitative online survey was conducted in March 2016, recruiting university students from North East Scotland via an all-student email. The anonymous questionnaire assessed student demographics (e.g. sex, ethnicity, age), STI testing behaviours, sexual risk behaviours, knowledge and five psychological constructs thought to be predictive of STI testing from theory and past research: attitudes, perceived susceptibility to STIs, social norms, social fear and self-efficacy. Results The sample contained 1294 sexually active students (response rate 10%) aged 18-63, mean age = 23.61 (SD 6.39), 888 (69%) were female. Amongst participants, knowledge of STIs and testing was relatively high, and students held generally favourable attitudes. 52% reported ever having an STI test, 13% intended to have one in the next month; 16% reported unprotected sex with more than one 'casual' partner in the last six months. Being female, older, a postgraduate, longer UK residence, STI knowledge, perceived susceptibility, subjective norms, attitudes and self-efficacy all positively predicted past STI testing behaviour (p < 0.01). Perceived susceptibility to STIs and social norms positively predicted intentions to have an STI test in the next month (p  < 0.05); perceived susceptibility also predicted past high-risk sexual behaviour (p < 0.01). Conclusions Several psychosocial predictors of past STI testing, of high-risk sexual behaviour and future STI intentions were identified. Health promotion STI testing interventions could focus on male students and target knowledge, attitude change, and increasing perceived susceptibility to STIs, social norms and self-efficacy towards STI-testing.